Stakeholder Political Ideology, Purpose of Business Beliefs, and Responses to CEO Activism: Introducing an Asymmetry Model - Nair, Krishnan; Mooijman, Marlon (Academy of Management Journal, 2026)
CEO activism refers to public stance-taking by CEOs on politically polarized issues. The prevailing view is that liberal and conservative stakeholders respond symmetrically to CEO activism, like how liberal and conservative voters have been found to respond to ideological causes. Specifically, both groups are thought to similarly favor ideologically aligned CEO activism, and disfavor ideologically misaligned CEO activism and non-activism. We question the assumption that liberal–conservative symmetry in national politics translates to stakeholder preferences. Extending research indicating that liberals scrutinize the perceived benefits and costs that businesses impose on society more than conservatives due to differences in purpose of business beliefs, we theorize that liberal stakeholders respond more favorably to aligned activism, and less favorably to misaligned activism and non-activism. We corroborate our ideological asymmetry model in three preregistered experiments examining job seekers and consumers. Crucially, conservatives, unlike liberals, prefer non-activism over aligned activism, even when conservatives feel strongly about the underlying issue. Experimentally reducing the liberal–conservative gap on purpose of business beliefs reduces these asymmetries. Our work challenges the assumption that liberal–conservative symmetry in politics translates to business; sheds new light on the strategic implications of CEO activism; and may explain the rarity of conservative CEO activism.